The Russian Revolution - Pipes, Richard, 1923-2018 (New York : Knopf, 1990)
Ground-breaking in its inclusiveness, enthralling in its narrative of a movement whose purpose, in the words of Leon Trotsky, was "to overthrow the world," The Russian Revolution draws conclusions that have already aroused great controversy in this country-and that are certain to be explosive when the book is published in the Soviet Union. Richard Pipes argues convincingly that the Russian Revolution was an intellectual, rather than a class, uprising; that it was steeped in terror from its very outset; and that it was not a revolution at all but a coup d'etat -- "the capture of governmental power by a small minority."
Includes bibliographical references (p. [915]-919) and index.
Donation of Anatole Shub
Keywords: Soviet Union -- History -- Revolution, 1917-1921.; Russia -- History -- Nicholas II, 1894-1917.